To Compare the Safety and Effectiveness of Subtenon’s Anesthesia (STA) Versus Peribulbar Anesthesia (PBA) in Cataract Surgery: Randomized Controlled Trial - Dr Vandana Parasar; Dr Soumyadeep Hazra; Dr Gyan Bhaskar, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Purpose: To compare the safety and effectiveness of Subtenon’s anesthesia (STA) versus Peribulbar anesthesia (PBA) in cataract surgery. Methods: A prospective randomized controlled trial was conducted on 88 patients (44 in each group) undergoing cataract surgery. Parameters assessed included pain scores (VAS), akinesia scores, intraoperative complications, and postoperative outcomes. Results: STA showed significantly lower pain scores during injection (2.1 ± 1.0 vs. 4.5 ± 1.2, p < 0.01) and comparable surgical comfort (p = 0.12). Akinesia was marginally better with PBA (p = 0.03), but STA had fewer complications (chemosis: 4.5% vs. 18.2%, p = 0.02). Both techniques provided adequate anesthesia for surgery. Conclusion: STA is a safer and equally effective alternative to PBA, with better patient comfort and fewer complications.